STUDI TENTANG PERSEPSI DAN PENGAMBILAN KEPUTUSAN PELANGGAN MUSLIM UNTUK BERALIH KE LAYANAN PREMIUM DI PLN UP3 KUDUS - Irfan Affandi; I Made Sukresna (ITB AAS INDONESIA Surakarta, 2022)
Electricity is one of the benchmarks for the progress of society and the nation. Electrical service providers must innovate to attract new customers and expand customer relationships. In an effort to provide excellent service, especially to customers, especially corporate customers, PT PLN (Persero) launched a new innovation product in the form of premium services. Premium service is a form of service provided by PT PLN with quality assurance, ensuring the reliability and certainty of the connection in accordance with the SLA (Service Level Agreement) agreed by PT PLN with customers as well as in UP3 Kudus. from a total of 361 existing medium voltage customers, only 7 customers switched to premium services with a percentage of 0.31%. With such a large gap, it is interesting to study what causes customers to still not want to switch to premium electricity services. The purpose of this study is to find out how the perceptions, knowledge, expectations, and intentions to buy PLN industrial customers towards the premium electricity services offered and to analyze the buying behavior of industrial customers in terms of external influences, internal influences and the purchasing decision-making process to switch from regular electricity services. to premium electricity service. The samples in this study were 4 medium voltage customers who had not switched to premium services and 4 customers who had switched to using premium services engaged in various business fields. Customers have a good perception that PLN's premium electricity services are the best in Central Java, especially for planned blackouts that can be well communicated by PLN. However, the problem in terms of price in each service matrix is ​​still considered by some customers to be burdensome and also in terms of the minimum operating hours requirement which is still a customer consideration. The expectation from PLN's industrial customers is that by switching to premium electricity services, the services provided must also be premium. In addition, customers also expect that this premium electricity service can accommodate only certain loads that require reliable and continuous supply quality, not for the entire production load so that the company does not need to shift all its burdens to premium electricity services. Keywords: Muslim consumer behavior, electricity, premium services.